Mini-review: Mitochondrial DNA methylation in type 2 diabetes and obesity - Rautenberg, Emma K.; Hamzaoui, Yassin; Coletta, Dawn K. (Frontiers in Endocrinology, 2022)
Type 2 diabetes (T2D) and obesity are two of the most challenging public health problems of our time. Therefore, understanding the molecular mechanisms that contribute to these complex metabolic disorders is essential. An underlying pathophysiological condition of T2D and obesity is insulin resistance (IR), a reduced biological response to insulin in peripheral tissues such as the liver, adipose tissue, and skeletal muscle. Many factors contribute to IR, including lifestyle variables such as a high-fat diet and physical inactivity, genetics, and impaired mitochondrial function. It is well established that impaired mitochondria structure and function occur in insulin-resistant skeletal muscle volunteers with T2D or obesity. Therefore, it could be hypothesized that the mitochondrial abnormalities are due to epigenetic regulation of mitochondrial and nuclear-encoded genes that code for mitochondrial structure and function. In this review, we describe the normal function and structure of mitochondria and highlight some of the key studies that highlight mitochondrial abnormalities in IR skeletal muscle of volunteers with T2D and obesity. Additionally, we describe epigenetic modifications in the context of IR and mitochondrial abnormalities, emphasizing mitochondria DNA (mtDNA) methylation, an emerging area of research.